2017
DOI: 10.5152/tao.2016.1852
|View full text |Cite
|
Sign up to set email alerts
|

Laryngomalacia: Our Clinical Experience

Abstract: Objective: The aim of this study is to analyse the clinical symptoms, follow-up and treatment properties of the laryngomalacia patients that we encountered between 2009 and 2014. Methods:Records of 81 laryngomalacia patients who were followed up in our clinic between 2009 and 2014 were retrospectively analysed. Patients' gender, age, time of onset of the symptoms, chief complaints, other co-existing congenital laryngeal anomalies and treatment and follow-up properties were evaluated. Results:Of the 81 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Bjornson and Johnson, & Denny et al, studies who reported that boys were affected more than girls (1.4:1) and young children between 6 months and 3 years of age more commonly than older children and adolescents [10,11]. Similarly, among the 81 laryngomalacia patients included in Olgun et al's study, 48 were male, and 33 were female, and the mean age was 4.9 months [12]. Also, among the total of 395 patients who were diagnosed with laryngomalacia and included in study by Irace et al, 92 (64.8%) were males, with a median (interquartile range) age at the time of study of 7.9 (3.2-20.5) months [13].…”
Section: Discussionmentioning
confidence: 92%
“…Bjornson and Johnson, & Denny et al, studies who reported that boys were affected more than girls (1.4:1) and young children between 6 months and 3 years of age more commonly than older children and adolescents [10,11]. Similarly, among the 81 laryngomalacia patients included in Olgun et al's study, 48 were male, and 33 were female, and the mean age was 4.9 months [12]. Also, among the total of 395 patients who were diagnosed with laryngomalacia and included in study by Irace et al, 92 (64.8%) were males, with a median (interquartile range) age at the time of study of 7.9 (3.2-20.5) months [13].…”
Section: Discussionmentioning
confidence: 92%